Multimodal Writing to Promote Global Competence for EFL Learners - Sezen Arslan (Sakarya University Journal of Education)
Multimodal writing refers to a process of writing with a combination of different modes such as visual, auditory, spatial, linguistic and textual. Research shows that multimodal writing has a positive effect on writing skills and learner motivation. Multimodal writing practices seem to be convenient for 21st-century language classrooms because learners are incredibly engaged in digital applications and they exchange information on multimedia platforms. The mere fact is that the scope of multimodal writing is not confined to teaching top-drawer writing skills including coherence, cohesion, fluency, and creativity but it should focus on promoting global competence. The learners need to have an understanding of the global challenges, concerns and intercultural issues so that they can be global-minded and take necessary steps for a sustainable world. Hence, in this study, the researcher reviews the literature and suggests practical ideas about how to implement multimodal writing to empower global competence.